Assessment of cell proliferation and prognostic factors in canine mammary gland tumors - Dutra,A.P. (2008)
Three methods for the analysis of cell proliferation, mitotic index/10 high-power fields (10 HPF), mitotic index/four sets of 10 HPF (40 HPF), and MIB-1 index were evaluated in a series of canine mammary gland tumors, as well as the possible correlation between them. Fifty-six canine mammary gland tumors, including 23 benign and 33 malignant, were studied. In addition, the prognostic impact of mitotic index/10 HPF, and histological malignancy grade were evaluated in 17 malignant tumors, being seven ductal and 10 metaplastic carcinomas. The three methods used to evaluate cell proliferation were correlated with the prognostic impact of mitotic index/10 HPF and histological malignancy grade. The results showed a strong association between mitotic figure counts and MIB-1 index (P<0.0001). A correlation was observed between mitotic count per 40 HPF and MIB-1, and between mitotic index per 10 HPF and 40 HPF (P<0.05). Moreover, histological malignancy grade and mitotic figure counts were excellent prognostic factors during three-year follow-up (P<0.05). There was a correlation between the three methods used for the evaluation of cell proliferation and prognostic factors as observed in human breast cancer studies.